EPIDEMIOLOGI FILARIASIS LIMFATIK DI KECAMATAN KOTA BESI, KABUPATEN KOTAWARINGIN TIMUR PROVINSI KALIMANTAN TENGAH - , Budi Setiawan, Prof. Dr. dr. Soeyoko, DTM&H., S.U ([Yogyakarta] : Universitas Gadjah Mada, 2013)
BACKGROUND. In Southeast Asia, as much as 60% of the population has been infected with filariasis. In 2008 as many as 11.699 cases has been reported. Distribution of the disease tends to spread in rural areas and epidemiological data needed about filariasis elimination program should be limited. AIM. The research aims to find out filariasis vector species with bionomic aspect, to find out the cause of lymphatic filariasis microfilarieae and the clinical symptoms of human patients with lymphatic filariasis. METHOD. This research conducted from February to June 2011, used descriptive observational study with 386 samples capillary blood at night by loop coils sampling. Collecting mosquitoes were done 10 times by landing collection method, using light traps and in the morning. RESULT. In all, 386 person (4 person mf-positive) were examined by the fingerprick method, the average density of microfilaria was 4.45, Mf rate is 1.04%, Acute Disease Rate is 5.44%, while Cronic Disease Rate is 0%. Brugia malayi was founded in four person mf-positive, microfilariae periodicity in this location is nocturnal periodic with harmonic waves and nocturnal sub-periodic with the non harmonic waves. Vector collection was founded 23194 mosquitoes are Mansonia uniformis (25.60%), Ma. Bonneae (20.70%), Culex tritaeniorhynchus (19.41%), An. maculatus (16.75%), An. balabacensis (15.27%), Ae. albopictus (1.39%), Ae. aegypti (0.88%). The highest density was caught in June with peak biting activity at 09:00 p.m to 10:00 p.m. However, this study not found L3 in the mosquitoes body. Conclusion. Filariasis occurring in Kotabesi is lymphatic filariasis caused by Brugia malayi, an infection in the evening related to the behaviour of mosquitoes acting as vectors.